2015
DOI: 10.1021/acs.orglett.5b01309
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereoselective Synthesis of Saccharin-Substituted β-Lactams via in Situ Generation of a Heterosubstituted Ketene and a Zwitterionic Intermediate as Potential Antibacterial Agents

Abstract: Highly stereoselective synthesis of saccharin derivatives containing functionalized 2-azetidinone moiety was achieved starting from saccharin as an available precursor. The approach to these valuable heterocyclic scaffolds involves a formal [2π + 2π] cycloaddition between Schiff bases and the saccharinylketene as a novel ketene which was generated in situ and an electrocyclic reaction of a zwitterionic intermediate. The identification of the ketene was confirmed by reaction with the stable free radical TEMPO (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Saccharin-substituted ketene 189, generated by carboxylic acid dehydration with Mukaiyama's reagent 186, reacted with imines to produce saccharin-substituted β-lactams, including 190 (Scheme 80), which was tested for biological activity. 120 Mukaiyama's reagent also was used to generate other ketenes for -lactam formation. Ketene 189 generated similarly also reacted with the stable free radical TEMPO forming 191, confirming the identity of the free ketene (Scheme 80).…”
Section: [2+2] Cycloaddition Reactions With Carbon-nitrogen Bonds -mentioning
confidence: 99%
See 1 more Smart Citation
“…Saccharin-substituted ketene 189, generated by carboxylic acid dehydration with Mukaiyama's reagent 186, reacted with imines to produce saccharin-substituted β-lactams, including 190 (Scheme 80), which was tested for biological activity. 120 Mukaiyama's reagent also was used to generate other ketenes for -lactam formation. Ketene 189 generated similarly also reacted with the stable free radical TEMPO forming 191, confirming the identity of the free ketene (Scheme 80).…”
Section: [2+2] Cycloaddition Reactions With Carbon-nitrogen Bonds -mentioning
confidence: 99%
“…Ketene 189 generated similarly also reacted with the stable free radical TEMPO forming 191, confirming the identity of the free ketene (Scheme 80). 120 The new triflyl-substituted ketene 192, generated by thermal diazoketone Wolff rearrangement, gives [2+2] cycloaddition with imines forming the corresponding substituted -lactams (Scheme 81).…”
Section: [2+2] Cycloaddition Reactions With Carbon-nitrogen Bonds -mentioning
confidence: 99%
“…The properties of the pseudosaccharins can be modified depending on which structures are combined with saccharin. In the case of tetrazole-saccharin, the properties of tetrazole, which can be very reactive, have been combined with saccharin, resulting in a greater stability of the tetrazole [12]. Furthermore, the combination of an allyl group with saccharin can also form compounds with the properties mentioned in previous paragraphs.…”
Section: Density Functional Calculations -Recent Progresses Of Theorymentioning
confidence: 99%
“…This can lead to challenges in the characterization of these compounds, since there could be a mixture of isomers whose population can become significant during the synthesis. As a result, there are signals in spectrophotometry [4,12,13] that cannot be associated with a precise isomer. Theoretical analysis can ease to obtain the different spectra of the possible isomers and the spectra could be weighted by a number or parameter, for example, a calculated molar fraction.…”
Section: Density Functional Calculations -Recent Progresses Of Theorymentioning
confidence: 99%
“…Their derivatives are important pharmaceuticals with a broad spectrum of biological activities and have been used as inhibitors of kinase 2 , human mast cell tryptase 3 and tyrosinase 4 , histone deacetylase 5 , α1a and α1c adrenergic receptor antagonists 6 , antianxiety and antibacterial agents. 7 More recently it has been shown that saccharin and saccharin-based compounds selectively bind to tumor-associated carbonic anhydrases. 8 Furthermore, saccharin forms salts with different active pharmaceutical ingredients resulting in highly water-soluble saccharinate, which can act as a potent sweetener able to mask the bitter taste of many drugs.…”
Section: Introductionmentioning
confidence: 99%